Louise Glück - the Nobel Prize for Literature 2020 (Confluenţe Bibliologice, 2020)
This article is dedicated to famous „Circe's Grief” poem by Louise Gluck, which is compared with several Russian poems. Circe is the main character of some of them. The structure of the poem makes Russian readers to remember Lermontov’s poem „The Dream”. The author speaks also about translation „Circe's Grief” poem in Russian language by Mizrahi, discusses myth, allusion and recognition of Louise Gluck’s „Circe's Grief”. Poetic power, wisdom and elegance of one of Gluck’s masterpieces makes us think about strong presence of her poetry in modern literature.
Keywords: the Nobel Prize in Literature 2020; Lоuise Gluck(1943); myth in literature